The 700-1500 cm-1 region of the S1 (A1-B-2) state of toluene studied with resonance-enhanced multiphoton ionization (REMPI), zero-kinetic-energy (ZEKE) spectroscopy,and time-resolved slow-electron velocity-map imaging (tr-SEVI) spectroscopy - Gardner, Adrian M.; Green, Alistair M.; Tamé-Reyes, Victor M.; Reid, Katharine L.; Davies, Julia A.; Parkes, Victoria H.K.; Wright, Timothy G. (American Institute of Physics, 2014)
We report (nanosecond) resonance-enhanced multiphoton ionization (REMPI), (nanosecond) zero-kinetic-energy (ZEKE) and (picosecond) time-resolved slow-electron velocity map imaging (tr-SEVI) spectra of fully hydrogenated toluene (Tol-h8) and the deuterated-methyl group isotopologue (α3-Tol-d3). Vibrational assignments are made making use of the activity observed in the ZEKE and tr-SEVI spectra, together with the results from quantum chemical andprevious experimental results.Here, we examine the 700–1500 cm−1 region of the REMPI spectrum, extending our previous work on the region ≤700 cm−1. We provide assignments for the majority of the S1 and cation bands observed, and in particular we gain insight regarding a number of regions where vibrations are coupled via Fermi resonance. We also gain insight into intramolecular vibrational redistribution in this molecule.